Identifying Futile Interfacility Surgical Transfers. Issue 8 (August 2017) - Broman, Kristy Kummerow; Phillips, Sharon E.; Ehrenfeld, Jesse M.; Patel, Mayur B.; Guillamondegui, Oscar M.; Sharp, Kenneth W.; Pierce, Richard A.; Poulose, Benjamin K.; Holzman, Michael D.
Surgeons perceive that some surgical transfers are futile, but the incidence and risk factors of futile transfer are not quantified. Identifying futile interfacility transfers could save cost and undue burdens to patients and families. We sought to describe the incidence and factors associated with futile transfers. We conducted a retrospective cohort study from 2009 to 2013 including patients transferred to a tertiary referral center for general or vascular surgical care. Futile transfers were defined as resulting in death or hospice discharge within 72 hours of transfer without operative, endoscopic, or radiologic intervention. One per cent of patient transfers were futile (27/ 1696). Characteristics of futile transfers included older age, higher comorbidity burden and illness severity, vascular surgery admission, Medicare insurance, and surgeon documentation of end-stage disease as a factor in initial decision-making. Among futile transfers, 82 per cent were designated as do not resuscitate (vs 9% of nonfutile, P < 0.01), and 59 per cent received a palliative care consult (vs 7%, P < 0.01). A small but salient proportion of transferred patients undergo deliberate care de-escalation and early death or hospice discharge without intervention. Efforts to identify such patients before transfer through improved communication between referring and accepting surgeons may mitigate burdens of transfer and facilitate more comfortable deaths in patients' local communities.